2001
DOI: 10.1177/14687984010013004
|View full text |Cite
|
Sign up to set email alerts
|

Sisters and Brothers as Language and Literacy Teachers: Synergy between Siblings Playing and Working Together

Abstract: Over the past three decades numerous studies from the English-speaking world have pointed to the advantages for young children of family involvement in their literacy development. However, their emphasis has always been firmly and almost exclusively upon parents working with children in specific ways and often using school-sanctioned materials. This article investigates the role played by young siblings close in age in each others' literacy development and argues for a unique reciprocity in learning between ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 19 publications
4
119
0
1
Order By: Relevance
“…'Scaffolding' has been further refined to afford a greater role to the child her or himself, using the term guided participation (Rogoff, 1990(Rogoff, , 2003. Studies on 'scaffolding' and 'guided participation' underpinned our argument for the synergy taking place between siblings where the younger sibling acts as an adjuvant to the older child's learning which takes place equally on both sides (Gregory, 2001;Gregory and Williams, 2000).…”
Section: Theoretical Framework and Backgroundmentioning
confidence: 99%
“…'Scaffolding' has been further refined to afford a greater role to the child her or himself, using the term guided participation (Rogoff, 1990(Rogoff, , 2003. Studies on 'scaffolding' and 'guided participation' underpinned our argument for the synergy taking place between siblings where the younger sibling acts as an adjuvant to the older child's learning which takes place equally on both sides (Gregory, 2001;Gregory and Williams, 2000).…”
Section: Theoretical Framework and Backgroundmentioning
confidence: 99%
“…However, the emphasis is still on the acquisition of skills from the children's side. Intergenerational computer activities seem, rather, to exhibit a reciprocal learning exchange that accords more closely with the concept of 'synergy' identified by Gregory (2001).…”
Section: Guided Participation and Synergymentioning
confidence: 85%
“…Synergy between siblings arises from the older child's greater knowledge being practised and re-formulated in order to share it with the younger sibling, who plays their part as active audience and questioner (Gregory, 2001). Interactions with grandparents around the computer introduce the additional possibility that the younger generation may have greater facility in operating this new cultural artefact, whilst the older generation has more experience in literacy and other areas of learning, and thus both parties may have knowledge to share.…”
Section: The Potential Of Ict For Early Learningmentioning
confidence: 99%
“…Literacy learning in particular is co-constructed between the learner and other members of the family or the community. Those members can be siblings (Gregory, 1998(Gregory, , 2001; grandparents (Jessel, Kenner, Gregory, Ruby, & Arju, 2011); or people with whom the learners interact in their daily activities (Volk & De Acosta, 2001). The Likert scale used with this study's participants showed that there is a low level of parental participation in their children's EFL learning at Jorge Abel Molina (JAM) School.…”
Section: Background Of Parental Involvement In Student Learning and Imentioning
confidence: 99%